The self-efficacy, self-regulation and academic motivation among students - Tarmizi S.N.A.; Ahmad R.; Sipon S.; Sawai R.P.; Mahyuddin M.K.; Tazzif M.H.; Khan A. (Indian Journal of Public Health Research and Development, 2024)
Indexed by SCOPUS